2017
DOI: 10.1016/j.adolescence.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent health literacy and health behaviors: A systematic review

Abstract: Objectives: To systematically review and synthesize literature on the relationship between health literacy and health behaviors in adolescents. Methods: Searches in PsychInfo, PUBMED/MEDLINE, and Educational Resources Information Center (ERIC) were conducted. Studies were included if they reported original data on the relationship between health literacy and a health behavior in adolescents, were written in English, and the population did not have a chronic illness or disability. Results: Seventeen studies met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
343
9
29

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(399 citation statements)
references
References 90 publications
(200 reference statements)
18
343
9
29
Order By: Relevance
“…They found that lower health literacy scores were associated with obesity, smoking, and poor self-reported nutrition behaviors [14]. Other reviews have confirmed possible associations between health literacy and different health behaviors in adolescents [15,16], although other determinants, such as psychosocial factors, may also play a large role alongside health literacy for the health outcomes of young adults [17].…”
Section: Introductionmentioning
confidence: 99%
“…They found that lower health literacy scores were associated with obesity, smoking, and poor self-reported nutrition behaviors [14]. Other reviews have confirmed possible associations between health literacy and different health behaviors in adolescents [15,16], although other determinants, such as psychosocial factors, may also play a large role alongside health literacy for the health outcomes of young adults [17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in their study on generic health literacy with n = 585 Korean adults aged 19 years and older, Lee et al [30] reported that males had more problems in understanding medical forms, directions on medication bottles, and written information offered by health care providers. Regarding health outcomes, research findings demonstrate that limited functional health literacy is associated with harmful and risky health behaviour in adolescence (e.g., nutritional and dieting habits, physical and sedentary activity, substance use, smoking, and alcohol use), whereas higher levels of media health literacy were positively associated with more health promoting behaviours [31]. Research on functional health literacy of adults associated limited levels with more hospitalizations, greater use of emergency care, limited use of early diagnosis and screening, reduced ability to interpret health messages, a poorer overall health status [32], and higher mortality rates in adulthood [33].…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, the importance of supportive environments has been emphasized to promote children's healthy lifestyles. According to Albert and Steinberg (2011), adolescents' decisions to participate in health behaviours are considerably susceptible to socioemotional factors (Fleary, Joseph, & Pappagianopoulos, 2018), particularly the peer group. The peer group, in particular, has been argued as one of major factors affecting adolescents' health literacy and health behaviour development (Manganello, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…They established their own criteria to distinguish useful health information from unreliable health information and shared the selected information with their friends and family members. In previous studies Nutbeam (2000Nutbeam ( , 2008 presented critical health literacy as one of the core concepts of health literacy, and Fleary et al (2018) noted that learning how to extract essential health messages from raw health information is vital for adolescents in developing critical health literacy and healthy behaviours. Given that a majority of research about health literacy is concentrated on functional health literacy and critical health literacy, it has rarely been investigated in the school context (Fleary et al, 2018).…”
Section: Discussionmentioning
confidence: 99%